An assessment of electrical deaths in the Western Cape Province from 2011 to 2020 - Chetty, Ansuya (Department of Pathology, 2025)
Electrical injury is a significant cause of morbidity and mortality worldwide. When an individual comes into contact with an electrical current, the resulting injury can range from minor burns to cardiac arrest and death. Electrical deaths are particularly concerning due to their sudden, unexpected nature, and the fact that they often occur in otherwise healthy individuals. This study aimed to explore the pathophysiology of electrical injury and its effects on regions of the human body. Two sets of data were examined to ascertain the prevalence and patterns of electrical deaths in the Western Cape Province of South Africa between 1 January 2011 and 31 December 2020.The first data set contained the variables of age, date of death, sex, suburb and blood alcohol concentration. The second data set was a retrospective review of autopsy reports from Salt River Mortuary, to provide an in-depth analysis of injury patterns and the circumstances surrounding these deaths. The medicolegal data from the Western Cape Province, South Africa were reviewed and the demographics analysed. A total of 401 cases of fatal electrocutions were identified, where the City of Cape Town was identified as a hotspot, reporting over 64% of these deaths. Males aged 21 to 30 years old were identified to be most vulnerable to electrical deaths. Medicolegal case files were reviewed retrospectively to obtain the demographics, circumstances and electrical sources of the electrocution fatalities at Salt River Mortuary (SRM) in Cape Town. A total of 102 cases were reviewed from SRM, where 370 joule burns were recorded in the electrical deaths. Electrical injury was primarily seen in the extremities and upper regions of the bodies. A variety of injuries were recorded including minor burns, deep burns and charring. The intensity and prevalence of injury was compared between males and females. Vulnerable demographics and prevalent circumstances surrounding electrical deaths were identified. The main electrical sources were live wires from exposure to illegal connections and cable theft. Ultimately, a better understanding of electrical injury can help to improve prevention and management strategies, leading to better outcomes for those affected by this devastating type of injury.